Protected Concerted Activity and Non-Unionized Employee Strikes: Worker Rights in Canada in the Time of COVID-19 - Slinn, Sara J. (Osgoode Hall Law Journal, 2020)
During the pandemic employees in the US have engaged in a wave of strikes, protests, and other collective action over concerns about unsafe working conditions, and many of these involved non-unionized workers in the private sector. Similar employee protests were notably absent in Canada. This article examines the differences in labour legislation between the US and Canada, which may help to explain these diverging experiences, primarily: the National Labor Relations Act (NLRA) section 7 protection for concerted activity, and the NLRA section 502 ability for a good faith strike due to abnormally dangerous conditions for work. This article outlines and compares the situation of, and consequences for, three categories of workers engaging in a strike over fears of workplace safety: unionized employees, non-unionized employees, and non-employees, such as independent contractors under the NLRA compared to under the Ontario Labour Relations Act (OLRA), as generally representative of Canadian labour legislation. In the final section, this article considers how a statutory provision similar to the NLRA protected concerted activity provision might be incorporated into Canadian labour legislation such as the OLRA. It also considers some more fundamental questions that such changes might prompt policymakers to reconsider, including: the focus of our statutory system on “organizing” collective action to the exclusion of “mobilizing” collective action, and questions about the potential role of minority unionism in our labour legislation system.